The Dietary Supplement Protandim(®) Decreases Plasma Osteopontin and Improves Markers of Oxidative Stress in Muscular Dystrophy Mdx Mice - Qureshi, Muhammad Muddasir (2010)
Therapeutic options for Duchenne muscular dystrophy (DMD), the most common and lethal neuromuscular disorder in children, remain elusive. Oxidative damage is implicated as a pertinent factor involved in its pathogenesis. Protandim(®) is an over-the-counter supplement with the ability to induce antioxidant enzymes. In this study we investigated whether Protandim(®) provided benefit using surrogate markers and functional measures in the dystrophin-deficient (mdx)mouse model of DMD. Male 3-week-old mdx mice were randomized into two treatment groups: control (receiving standard rodent chow) and Protandim(®)-supplemented standard rodent chow. The diets were continued for 6-week and 6-month studies. The endpoints included the oxidative stress marker thiobarbituric acid-reactive substances (TBARS), plasma osteopontin (OPN), plasma paraoxonase (PON1) activity, H&E histology, gadolinium-enhanced magnetic resonance imaging (MRI) of leg muscle and motor functional measurements. The Protandim(®) chow diet in mdx mice for 6 months was safe and well tolerated. After 6 months of Protandim(®), a 48% average decrease in plasma TBARS was seen; 0.92 nmol/mg protein in controls versus 0.48 nmol/mg protein in the Protandim(®) group (p = .006). At 6 months, plasma OPN was decreased by 57% (p = .001) in the Protandim(®)-treated mice. Protandim(®) increased the plasma antioxidant enzyme PON1 activity by 35% (p = .018). After 6 months, the mdx mice with Protandim(®) showed 38% less MRI signal abnormality (p = .07) than mice on control diet. In this 6-month mdx mouse study, Protandim(®) did not significantly alter motor function nor histological criteria.